2021
DOI: 10.3389/fendo.2021.624423
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ramadan Diurnal Intermittent Fasting on Hypoglycemic Events in Patients With Type 2 Diabetes: A Systematic Review of Randomized Controlled Trials and Observational Studies

Abstract: Ramadan is the 9th month of the lunar calendar during which Muslims abstain from food and drink between dawn and sunset for 30 consecutive days. Ramadan fasting is observed by all healthy Muslim adults, as well many Muslims with type 2 diabetes (T2DM). Hypoglycemic events (HE) are a serious complication associated with diabetes management and are associated with increased cardiovascular disease risk. Conflicting results have been reported concerning the incidence of HE among people with T2DM observing Ramadan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 115 publications
1
33
0
Order By: Relevance
“…While the effect of fasting (and its associated higher sugar intake) did not show any adverse glucometabolic impacts in healthy subjects (64), its effects on diabetic patients remains to be elucidated. Worldwide, it is estimated that 70 million people with diabetes observe fasting during Ramadan (65). Considering this large population of patients who mostly selfdecide to fast during Ramadan, despite being exempted to do so as per the Islamic rules of Ramadan, the findings of this study (higher sugar consumption during the month of Ramadan) ought to be integrated into the formulation of culturespecific recommendations for dietary intake during the month of Ramadan for this group of patients.…”
Section: Discussionmentioning
confidence: 95%
“…While the effect of fasting (and its associated higher sugar intake) did not show any adverse glucometabolic impacts in healthy subjects (64), its effects on diabetic patients remains to be elucidated. Worldwide, it is estimated that 70 million people with diabetes observe fasting during Ramadan (65). Considering this large population of patients who mostly selfdecide to fast during Ramadan, despite being exempted to do so as per the Islamic rules of Ramadan, the findings of this study (higher sugar consumption during the month of Ramadan) ought to be integrated into the formulation of culturespecific recommendations for dietary intake during the month of Ramadan for this group of patients.…”
Section: Discussionmentioning
confidence: 95%
“…However, the findings of other studies suggested that RF could increase the risk of hypoglycaemia in some of these patients, while could not in others (26)(27)(28). This variation could be ascribed to many factors such as season of Ramadan month, fasting time duration, pre-fasting education, geographical location and the duration of time since diagnosis with the disease (29). Thus, this review has hypothesised that some children who are eligible to fast according to Islamic regulations on RF, which usually starts around 12 years old or reaching puberty, will benefit from RF and the effects could be the same as in adults.…”
Section: Introductionmentioning
confidence: 91%
“…Every year, the Islamic holy month of Ramadan is observed by more than 1.5 billion Muslims worldwide (Abdelrahim et al 2021). During Ramadan, Muslims must refrain from eating, drinking, smoking, and sexual activity from dawn to dusk each day, for about 11-22 hours depending on the geographical location and solar season.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant and lactating women, children before puberty, and those with certain health conditions such as patients with diabetes are exempt from fasting during Ramadan; however, some of these groups still choose to fast during Ramadan and may face complications (Abdelrahim et al 2021). Therefore, the impact of RIF has been extensively researched regarding medical recommendations for these population groups (Hassanein et al 2022; Mahmood et al 2022).…”
Section: Introductionmentioning
confidence: 99%